The emergence and early development of self-regulation in young children - Whitebread, David; Basilio, Marisol (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
It is amply recognised in the literature that metacognitive and self-regulatory abilities are of fundamental significance for children’s general and academic development, and also, that these abilities are highly teachable. When do these skills emerge and how do they develop are questions still open to debate, and therefore, subject to new evidence accumulated in the field. In this paper we aim to provide a general overview of the significant advances in the last decade of research regarding the development of self-regulation in children from birth to six years of age. We review evidence suggesting that these abilities begin their development right from infancy and through the preschool years. In the first two sections we address the early emergence of executive functioning and cognitive control, and early emotional and social regulation. The final section deals with a significant and newly emerging area of research, concerned with early communicative and symbolic tools and the key role they play in the emergence of self-regulatory abilities in young children. We discuss the theoretical, methodological and educational significance of this body of research.